Obesity Treatments to Improve Type 1 Diabetes (OTID): a randomized controlled trial of the combination of glucagon-like peptide 1 analogues and sodium-glucose cotransporter 2 inhibitors—protocol for Obesity Treatments to Improve Type 1 Diabetes (the OTID trial) - Ebaa Al-Ozairi; Kavita Narula; Alexander D. Miras; Etab Taghadom; Abeer El Samad; Jumana Al Kandari; Anas Alyosef; Anant Mashankar; Werd Al-Najim; Carel W. le Roux (Trials, 2024)
Abstract Background The guidelines of the American Diabetes Association and European Association for the Study of Diabetes suggest that patients with obesity type 2 diabetics and chronic kidney disease need either glucagon-like peptide 1 receptor analogues or sodium-glucose cotransporter-2 inhibitors. If neither achieve metabolic control, then the recommendation is to combine both drugs. The evidence base for combining glucagon-like peptide 1 receptor analogues and sodium-glucose cotransporter-2 inhibitors is not well researched, and hence, the impact of the guidelines is limited. The aim of this randomized controlled trial is to test the impact of the combination of glucagon-like peptide 1 receptor analogues/sodium-glucose cotransporter-2 inhibitors on body weight and kidney damage, in patients with type 1 diabetes and chronic kidney disease. In addition, we will explore the associated changes in the metabolic pathways with each of the treatments used in this randomized controlled trial. Methods In this 6-month randomized control trial, 60 participants aged between 21 and 65 years, with a body mass index above 25 kg/m2, and type 1 diabetics with chronic kidney disease will be randomized to receive 1 of 5 possible treatments: (1) standard care (control), (2) glucagon-like peptide 1 receptor analogues alone, (3) sodium-glucose cotransporter-2 inhibitors alone, (4) combination of glucagon-like peptide 1 receptor analogues and sodium-glucose cotransporter-2 inhibitors and (5) combination of glucagonlike peptide 1 receptor analogues and sodium-glucose cotransporter-2 inhibitors with intensive lifestyle advice. The primary objective will be the percentage change in total body weight from baseline at 6 months. The secondary objectives are to compare the change in glycaemia; blood pressure; dyslipidaemia; albuminuria; proportion of participants reaching weight loss of ≥ 5%, ≥ 10% and ≥ 15%; and change in BMI (kg/m2) from baseline and change in waist circumference (cm). All the experiments will be conducted at the Dasman Diabetes Institute after approval from the local research and ethics committee. Discussion The present randomized controlled trial aims to investigate the impact of the combination of glucagon-like peptide 1 receptor analogues and sodium-glucose cotransporter-2 inhibitors on body weight and kidney damage in patients with type 1 diabetes mellitus and chronic kidney disease, as well as exploring the associated changes in the metabolic pathways with each of the treatments used. This study addresses the current gap in the evidence base regarding the combination of these two drugs, which is particularly relevant given the American Diabetes Association and European Association for the Study of Diabetes guidelines recommending their combined use for patients with obesity, type 2 diabetes, and chronic kidney disease who do not achieve metabolic control with either drug alone. Trial registration ClinicalTrials.gov Identifier: NCT05390307 Trial registration date - 25th May 2022